2018
DOI: 10.1186/s12902-018-0322-7
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodine treatment for graves’ disease: a 10-year Australian cohort study

Abstract: BackgroundRadioactive iodine (I131) is a common definitive treatment for Graves’ Disease. Potential complications include worsening, or new development of Graves’ eye disease and development of a radiation thyroiditis. The purpose of the present study was to assess outcomes of patients treated with I131 in an Australian tertiary centre over 10 years.MethodsData from 101 consecutive patients treated with I131 for a diagnosis of Graves’ disease between 2005 to 2015 was collected and reviewed retrospectively. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 23 publications
(43 reference statements)
4
32
1
2
Order By: Relevance
“…In most studies remission is defined as normal serum TSH, FT4, and triiodothyronine (T3) serum concentrations lasting for 1 year without any treatment. But in a recent Australian study, remission was defined as euthyroidism or hypothyroidism after 12 months, and it was reported that 79% of patients achieved “remission” with a single dose of 131 I [ 16 ].…”
Section: Radioactive Iodinementioning
confidence: 99%
“…In most studies remission is defined as normal serum TSH, FT4, and triiodothyronine (T3) serum concentrations lasting for 1 year without any treatment. But in a recent Australian study, remission was defined as euthyroidism or hypothyroidism after 12 months, and it was reported that 79% of patients achieved “remission” with a single dose of 131 I [ 16 ].…”
Section: Radioactive Iodinementioning
confidence: 99%
“…TRAb becomes negative in patients who achieve disease remission on ATD therapy, and persistence of TRAb predicts ATD therapy failure (27,28). It has also been reported that high TRAb level may be associated with RAI treatment failure (29,30,31). As a result, patients who have persistent TRAb levels after ATD therapy may have higher TRAb levels prior to RAI treatment, and this may explain treatment refractoriness to both therapies.…”
Section: Discussionmentioning
confidence: 99%
“…This figure was lower than reported in the previous studies using the estimation method to determine I-131 activity with the success rate between 60-85%. 10,11,[14][15][16][17][18] Several factors affected our therapeutic outcome. The first important factor that affected the outcome was thyroid gland size, well known to be an independent predictor of the response to I-131 therapy.…”
Section: Discussionmentioning
confidence: 99%